Young People’s Engagement with News: Media Literacy and Representations Through Vlogging - Li, Jiaxin (Transactions on Social Science, Education and Humanities Research, 2023)
This paper explores the intricate connection between media and citizenship, particularly focusing on the younger generation’s deep involvement with digital media platforms. The concept of media literacy is examined as a potential solution to the challenges of engaging youth with news and mitigating the spread of fake news. The paper highlights the limitations of traditional media literacy approaches in addressing contemporary media issues and suggests new strategies to enhance media literacy among young people.